A Tale of a Trail on How It Takes 5 Days of Kawasaki Disease to Initiate Coronary Artery Injury and Change the Lives of Children - Nagib Dahdah (AVES Yayincilik, 2024)
Many articles written on Kawasaki disease explain the disease and the history of an acute inflammatory dysregulation that typically affects preschool children and does not spare older ones. Six decades have passed since the discovery of the disease in Japan, yet there are parts of the world where the disease passes unacknowledged, diagnosis is delayed, or basic treatments are not readily available. The burden of Kawasaki disease is on every health-care provider who attends to children's health. It takes 5 days for the disease to initiate coronary artery injury in a child's heart, compared to 5 decades of lifetime atherosclerosis. Challenges facing patients, families, and physicians may not be overcome unless we advocate for the disease recognition and seek support for affordable, timely treatment, impactful research, and dissemination of knowledge. The purpose of this review is to provide a comprehensive review of the history of Kawasaki disease and how it has affected children's health worldwide over the last 6 decades. The review also raises current challenges facing the fight against Kawasaki disease. In an effort to bring Kawasaki disease advocates together in a landing zone, an internet hub for Kawasaki disease experts and enthusiasts has been created: the International Kawasaki Disease Society (presently a concept idea) and a dedicated website, www.ikds-org.